The role of regenerative medicine in the treatment of sports injuries - Malanga, G.; Nakamura, R. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Traditional treatment of sports injuries includes use of the PRICE principle (Protection, Rest, Ice, Compression,Elevation), nonsteroidal anti-inflammatories, physical therapy modalities, and corticosteroid injections. Recent evidence has raised concerns over this traditional treatment approach regarding the use of anti-inflammatories and injectable corticosteroids. More recent treatments, known as regenerative medicine, include platelet-rich plasma and stem cell therapies. Evidence for their efficacy in a variety of sports injuries has emerged, ranging from tendinopathy and muscle tears to ligament and chondral injuries. This article reviews the literature regarding established treatments for sports injuries and these more innovative treatments.